The Evolution and History of PR Technologies: A Comprehensive Analysis - Ramanova Gulnoza Ibragimovna (Zien Journals, 2023)
This scientific article provides a comprehensive analysis of the history and evolution of public relations (PR) technologies. Over the years, PR has witnessed significant transformations due to advancements in technology, reshaping the way organizations communicate and engage with their stakeholders. This article traces the development of PR technologies from traditional methods to modern digital platforms, exploring their impact on the field of public relations. It examines key milestones, innovations, and trends that have shaped PR technologies, highlighting their benefits, challenges, and future prospects.
Keywords: Print and broadcast media era; Print publications; Radio